Semiotics at Discursive Texts and Images in Online News - Heryono, Heri; Faisal, Helmy; ., . (International Journal of Engineering and Technology, 2018)
The paper established an inappropriate relationship of text and image that should interact in one whole package of online news. It applied Semiotics analysis to go under the problems occurred. The analysis was developed to respond the question: why should be the text and image in online news associated? Do they match? Developed in three levels of analysis processes-analysis of relevant engagement in text and image; extended analysis of discursive relationship involved in news that turned to hoax; the intention of attaching the misplaced image to the text. This paper used qualitative Semiotics analysis to illustrate malfunction of text and image in online news. It is wished to be able to enhance the accuracy of a news.Â Â